2000
DOI: 10.1007/s001250051520
|View full text |Cite
|
Sign up to set email alerts
|

High glucose modulates P2X 7 receptor-mediated function in human primary fibroblasts

Abstract: Extracellular ATP triggers a variety of responses in several cell types, including contraction of smooth muscle cells [1], regulation of nitric oxide production from endothelium [2], stimulation of cytokine release from immune cells [3,4], and modulation of several other metabolic pathways [5,6]. Moreover, it is a strong stimulus for insulin release from isolated pancreas and beta cells [7,8], which points to a potentially important role for this nucleotide in the control of blood glucose. Recently, ATP recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 25 publications
4
42
0
2
Order By: Relevance
“…5, B-D). The activation of P2X 7 receptor also triggers plasma membrane depolarization caused by transmembrane cation influx (25). Therefore we monitored the change in membrane potential using a fluorescent potentialsensitive anionic dye, DiBAC 4 (3).…”
Section: P2x 7 Receptor-induced Cell Death Is Mediated By CLmentioning
confidence: 99%
“…5, B-D). The activation of P2X 7 receptor also triggers plasma membrane depolarization caused by transmembrane cation influx (25). Therefore we monitored the change in membrane potential using a fluorescent potentialsensitive anionic dye, DiBAC 4 (3).…”
Section: P2x 7 Receptor-induced Cell Death Is Mediated By CLmentioning
confidence: 99%
“…Its systemic concentrations are used as a marker for adverse prognosis [8]. Fibroblasts are not only the major contributor to collagen biosynthesis, but also participate in plaque remodelling via expression and release of MMP2 and MMP9 [9]; moreover, they release abundant amounts of IL6, particularly in the presence of high glucose concentrations [10]. It has been repeatedly shown that primary skin fibroblasts exhibit at least some of the characteristics and functional properties of vascular wall cells [11,12] and share with them a common genesis [13].…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of glucose potentiate these P2X7-mediated responses [84] . This effect of glucose is attributed to a redistribution of P2X7 on the cell surface rather than increased expression of this receptor [84] . Of note, skin fibroblasts from type 2 diabetic subjects demonstrate enhanced P2X7-mediated responses compared to skin fibroblasts from normal subjects [85] .…”
Section: Fibroblastsmentioning
confidence: 99%
“…Human skin fibroblasts express P2X7 [83,84] . In addition to cation fluxes, dye uptake and membrane depolarisation, P2X7 activation in these cells results in microvesiculation, process elongation, IL-6 release and apoptosis [84] . High concentrations of glucose potentiate these P2X7-mediated responses [84] .…”
Section: Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation